Parents income and nutritional status of toddlers during the covid-19 pandemic - Amanah, Nur Umi; Sulistyorini, Lantin; Juliningrum, Peni Perdani; Rahmawati, Iis; Merina, Nuning Dwi (Universitas Muhammadiyah Semarang, 2023)
The nutritional status of a toddler can be influenced by a parent's income because meeting the nutritional needs of a toddler, is very dependent on parent's income. This study aims to analyze the Relationship between Parent's Income and Nutritional Status of Toddlers During the Covid-19 Pandemic at the Integrated Health Post in Alassumur Kulon Village, Kraksaan District, Probolinggo Regency District, Probolinggo Regency. The research design used was an analytic observational design, with a cross-sectional research design. The number of samples was 80 respondents with the purposive sampling method. This study uses univariate analysis to determine the frequency distribution and bivariate analysis using Spearman's Rho test. The results show that most of the parents' income is in the medium category, with as many as 31 respondents (38.8%). Most of the nutritional status of toddlers is in the good nutrition category, with as many as 46 respondents (57.5%). The results showed that there was a Relationship between Parent's Income and the Nutritional Status of Toddlers During the Covid-19 Pandemic at the Integrated Health Post in Alassumur Kulon Village, Kraksaan District, Probolinggo Regency with a p-value of 0.000 (<0.05), so Ha was accepted. The conclusion is that the income of parents affects the availability of food and the fulfillment of nutritional intake which has an impact on the nutritional status of toddlers. The role of parents in efforts to fulfil children's nutritional intake is very important, managing their finances while still paying attention to the nutritional needs of children is the key to success in maintaining the good nutritional status of toddlers.